Reviving House of National Representatives Power: A Normative Analysis Through the Lens of Fiqh Siyasah Dusturiyah - Priyanto, Ari; Al arif, M. Yasin; Faizal, Liky; Sofiana, Anis (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
This research aims to strengthen the institution of the House of National Representatives (DPD) in the national legislation programme, to be more representative in accommodating national aspirations. Through a normative juridical approach and analysis of Siyasah duturiyah, this research examines the principles of justice, deliberation, and participation under the values of Sharia in public policy making. This research is normative juridical research by collecting primary and secondary legal materials relevant to the research utilizing a statutory approach and conceptual approach in both positive law and siyasah duturiyah. The results found that to strengthen the control and development of DPD in the national legislation, it is necessary to amend the 1945 Fundamental law of the Republic of Indonesia, revise the Law No. 17/2014, revise the Law No. 27/2009, separate arrangements regarding the assignment and functions of DPD, adopt a strong bicameral system and likely bicameral. The impact is hoped to enrich the study in the field of Fiqh Siyasah and Fundamental law, especially in the context of developing a more inclusive legislative system under the framework of the Unitary Republic of Indonesia.